﻿Matrix metalloproteinase-9 expression is a marker of aggressive esophageal carcinoma: a meta-analysis - Tullavardhana, Thawatchai; Akkranurakul, Prinya; Ungkitphaiboon, Withoon; Songtish, Dolrudee (European Journal of Oncology and Environmental Health, 2016)
Background: Matrix metalloproteinase-9 (MMP-9) is the proteolytic enzyme degrades type IV collagen in basement membrane causing tumor invasion and metastasis. The purpose of the study is to evaluate whether MMP-9 expression is associated with aggressiveness of esophageal carcinoma.Method: A search was performed on Pubmed, EMBASE, Google scholar and the Cochrane database until March 2014. A meta-analysis was conducted to investigate the association between MMP-9 expression and clinicopathological characteristics of esophageal cancer.Result: The final analysis included 673 esophageal cancer patients from 9 studies. MMP-9 expression was determined on biopsy or surgical specimens by IHC. The pooled data demonstrated that positive MMP-9 expression was significantly associated with poorer tumor differentiation (OR = 1.71, 95% CI: 1.13, 2.58; p = 0.01), lymph node metastasis (OR = 1.80, 95% CI: 1.20, 2.71; p = 0.005) and vascular invasion (OR = 2.55, 95% CI: 1.54, 4.21; p = 0.003). However, there were no significant associations between MMP-9 expressions and advanced tumor staging, depth of tumor invasion and lymphatic invasion.Conclusion: The expression of MMP-9 is associated with poorer tumor differentiation, lymph node metastasis and vascular invasion. MMP-9 expression could be a valuable marker for aggressiveness of esophageal cancer.